Characterization of the complete chloroplast genome of Salvia Przewalskii Maxim. (Lamiaceae), a substitute for Dan-Shen Salvia miltiorrhiza Bunge. Issue 1 (2nd January 2019) - Du, Yan; Wang, Yuan-Yuan; Xiang, Chun-Lei; Yang, Mei-Qing
Abstract: The complete cp genome of Salvia przewalskii was 152, 678 bp in length, including a large single copy region (LSC) of 84, 102 bp, a small single copy region (SSC) of 17, 638 bp and a pair of inverted repeats (IRs) of 25, 469 bp. The genome contained 131 genes, including 86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The overall GC content of this genome was 38.0%, with the corresponding values of LSC, SSC, and IR regions being 36.2, 31.9, and 43.2%, respectively. Further, the phylogenomic analysis of Mentheae strongly supported the sister relationship of Salvia przewalskii and Salvia miltiorrhiza .